8 - Leading an Academic Staff Union as a Middle-level Academic (2003–2013) - Wafula, Richard Makhanu (Journal of Higher Education in Africa, 2022)
This article examines the emergence of the author as a leader of the Universities Academic Staff Union at a university in East Africa. Using the role, resource and constraint-based theories as well as autoethnography, which is a sub-category of qualitative research, the author traces the intellectual and political ferment that enabled him to become a unionist. From the discussion that emanated from the data he collected, from memos, newspaper articles and personal memories, it became increasingly clear that as a unionist his story demonstrates tensions, contestations and in some cases expensive trade-offs. Overall, there were actions that he performed well and others that he would implement differently were he given a second chance to lead the union.